2017
DOI: 10.7249/rr1588
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Promising Approaches to U.S. Army Institutional Change: A Review of the Literature on Organizational Culture and Climate

Abstract: This document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For information on reprint and linking permissions, please… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Creating a fair and inclusive organization that values different backgrounds and perspectives and thus attracts, recruits, and retains the best talent available. 20 We are professionals. We wear a uniform.…”
Section: People-related Practicesmentioning
confidence: 99%
“…Creating a fair and inclusive organization that values different backgrounds and perspectives and thus attracts, recruits, and retains the best talent available. 20 We are professionals. We wear a uniform.…”
Section: People-related Practicesmentioning
confidence: 99%
“…(Schein, 1990, p. 111) Schein's definition captures how culture is transmitted across generations. In 2017, a team of RAND analysts identified drivers that can bring about organizational culture and climate changes for the U.S. Army: goals, accountability, training, resources, and engagement (Meredith et al, 2017). Using the framework, we developed four sets of recommendations to help the Coast Guard address each of these aspects.…”
Section: Recommendations To Improve the Coast Guard Climate In Suppor...mentioning
confidence: 99%
“…Therefore, the culture change requires concerted efforts to intervene in the transmission of undesirable assumptions. In 2017, a team of RAND analysts identified drivers that can bring about organizational culture and climate changes for the U.S. Army (Meredith et al, 2017). The RAND team developed a framework of culture change driven by five factors: goals, accountability, training, resources, and engagement.…”
Section: Conclusion and Recommendations To Improve The Coast Guard Cl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in culture may be achieved, in part, through command emphasis (e.g., Meredith et al, 2017). GAO (2016) found that use of specific virtual training devices was highest when training strategies prescribed use of the devices, and, as reported in Chapter Four, command emphasis was associated with high utilization of SBT systems.…”
Section: Revise Training Policy and Strategymentioning
confidence: 99%